2013
DOI: 10.1073/pnas.1220710110
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-126–mediated control of cell fate in B-cell myeloid progenitors as a potential alternative to transcriptional factors

Abstract: Lineage specification is thought to be largely regulated at the level of transcription, where lineage-specific transcription factors drive specific cell fates. MicroRNAs (miR), vital to many cell functions, act posttranscriptionally to decrease the expression of target mRNAs. MLL-AF4 acute lymphocytic leukemia exhibits both myeloid and B-cell surface markers, suggesting that the transformed cells are Bcell myeloid progenitor cells. Through gain-and loss-of-function experiments, we demonstrated that microRNA 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 46 publications
3
29
0
Order By: Relevance
“…Sustained miRNA-126 expression has direct effects on the B cell precursor compartment, including early lymphoid lineage priming (Okuyama et al, 2013), increased proliferation (Lechman et al, 2012), and-as shown in this work-reduced levels of apoptosis and delayed differentiation toward mature B cells. It is likely that collaborating mutations occur at the level of multipotent progenitors and/or B cell precursors in order to induce full-blown leukemia, and additional studies are warranted to define their nature and hierarchical occurrence in distinct progenitor cell subpopulations during the pre-leukemic phase in our model.…”
Section: Discussionsupporting
confidence: 65%
“…Sustained miRNA-126 expression has direct effects on the B cell precursor compartment, including early lymphoid lineage priming (Okuyama et al, 2013), increased proliferation (Lechman et al, 2012), and-as shown in this work-reduced levels of apoptosis and delayed differentiation toward mature B cells. It is likely that collaborating mutations occur at the level of multipotent progenitors and/or B cell precursors in order to induce full-blown leukemia, and additional studies are warranted to define their nature and hierarchical occurrence in distinct progenitor cell subpopulations during the pre-leukemic phase in our model.…”
Section: Discussionsupporting
confidence: 65%
“…Simultaneously, the activation and proliferation of CD4 + SP cells also changed significantly. Similarly, miR-126 has also been reported to regulate the development of B cells from B cell progenitor cells [15]. Moreover, Agudo et al [16] found that miR-126 is critical for the survival and function of plasmacytoid dendritic cells (pDCs) and is involved in innate immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that miR-126 is also involved in the development and function of some types of immune cells [13,14]. For example, Okuyama et al [15] found that miR-126 is an important regulator in the development of B cells through controlling their expansion and proliferation, which alters the proportion of B cells from hematopoietic progenitor cells (HPCs) in the absence of early B-cell factor 1 (EBF1). Furthermore, Agudo et al [16] reported that miR-126 regulates the function of plasmacytoid dendritic cells (pDCs) and participates in the innate immune response induced by viruses and other microorganisms by targeting vascular endothelial growth factor receptor 2 (VEGFR2).…”
Section: Cd4mentioning
confidence: 99%
“…However, mice lacking miR-181 exhibited a modest impairment in B cell development only [22, 23], suggesting that the impact of miR-181 in B cell development remains to be elucidated. In addition, overexpression of miR-126 retrovirus in an immature B cell line derived from an acute lymphoblastic leukemia patient, and in mouse lin − HSPCs induced B cell differentiation through the regulation of insulin regulatory subunit-1 (IRS-1), an inhibitor of differentiation and proliferation [24]. However, how IRS-1 regulates B cell differentiation remains undetermined [24].…”
Section: Mirnas In B Cell Lineage Commitment: Mir-126 Mir23a Mir-132mentioning
confidence: 99%